The instruments for measuring QoL in hemodialysis patients: A scoping review - Baiq Reny Ermayuningsih; Iis Rahmawati; Muhammad Zulfatul A'la (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Quality of life (QoL) is a crucial indicator for evaluating the well being of patients undergoing hemodialysis, encompassing physical, psychological, social, and environmental dimensions. Accurate measurement of QoL serves as a fundamental basis for clinical decision making, care planning, and the development of patient centered policies. Purpose: To identify, synthesize, and analyze the instruments used to measure QoL in hemodialysis patients within the international literature. Method: The PRISMA-ScR approach, employing a systematic search across four major databases: ProQuest, BMC, PubMed, Wiley, and other sources. The search yielded seven articles that met the inclusion criteria and were subsequently analyzed thematically. Results: Seven primary instruments were identified, namely the KDQOL-SF™, KDQOL-36, QDIS-7, HARQ, WHOQOL-BREF, EQ-5D-5L, and the Caregiver Quality of Life Inventory. Each instrument demonstrated specific strengths related to construct design, contextual applicability, and target population, with adequate validity and reliability. However, variations in dimensional coverage, limited cross cultural validation, and a predominance of cross-sectional designs without longitudinal evaluation were observed. Conclusion: The findings highlight the importance of contextual adaptation, multi-cultural validation, and integration of QoL instruments into clinical evaluation systems. They also provide a foundation for developing more responsive and culturally relevant tools to improve care quality and patient well-being.